2021
DOI: 10.3389/fnut.2021.770489
|View full text |Cite
|
Sign up to set email alerts
|

Claims on Ready-to-Eat Cereals: Are Those With Claims Healthier?

Abstract: Background: The use of advertising content strategies that suggest consuming a product will confer nutrient- and health-related benefits influences household food purchasing decisions, which increases consumption of energy-dense, nutrient-poor products. We examined the presence of marketing claims regarding nutrient content, health and nature in ready-to-eat (RTE) cereal packages in relation to the products' nutritional quality.Methods: A cross-sectional content analysis was conducted on 178 RTE cereal package… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…The latter may be seen as a positive characteristic, but it does not correct the risk for NCDs associated with the overall composition of the products. Other analyses carried out in Colombia showed that 57.3% of analyzed ready-to-eat cereals had nutrient-content claims but at the same time were high in energy (93–99.9%) and sugar (88–93%) [ 60 ]. In Mexico, most of the UPPs with added micronutrients are baby foods (95%), ready-to-eat breakfast cereals (62.9%), and sandwich bread and tortillas (56.3%); these UPPs with added micronutrients were more likely to contain excessive free sugars and non-nutritive sweeteners [ 48 ].…”
Section: Large-scale Food Fortification and Market-driven Fortificati...mentioning
confidence: 99%
“…The latter may be seen as a positive characteristic, but it does not correct the risk for NCDs associated with the overall composition of the products. Other analyses carried out in Colombia showed that 57.3% of analyzed ready-to-eat cereals had nutrient-content claims but at the same time were high in energy (93–99.9%) and sugar (88–93%) [ 60 ]. In Mexico, most of the UPPs with added micronutrients are baby foods (95%), ready-to-eat breakfast cereals (62.9%), and sandwich bread and tortillas (56.3%); these UPPs with added micronutrients were more likely to contain excessive free sugars and non-nutritive sweeteners [ 48 ].…”
Section: Large-scale Food Fortification and Market-driven Fortificati...mentioning
confidence: 99%